Reliability and validity of a Mediterranean diet and culinary index (MediCul) tool in an older population with mild cognitive impairment. Issue 10 (7th November 2018) - Radd-Vagenas, Sue; Fiatarone Singh, Maria A.; Inskip, Michael; Mavros, Yorgi; Gates, Nicola; Wilson, Guy C.; Jain, Nidhi; Meiklejohn, Jacinda; Brodaty, Henry; Wen, Wei; Singh, Nalin; Baune, Bernhard T.; et al.
Abstract: Dementia is a leading cause of morbidity and mortality without pharmacologic prevention or cure. Mounting evidence suggests that adherence to a Mediterranean dietary pattern may slow cognitive decline, and is important to characterise in at-risk cohorts. Thus, we determined the reliability and validity of the Mediterranean Diet and Culinary Index (MediCul), a new tool, among community-dwelling individuals with mild cognitive impairment (MCI). A total of sixty-eight participants (66 % female) aged 75·9 (sd 6·6) years, from the Study of Mental and Resistance Training study MCI cohort, completed the fifty-item MediCul at two time points, followed by a 3-d food record (FR). MediCul test–retest reliability was assessed using intra-class correlation coefficients (ICC), Bland–Altman plots and κ agreement within seventeen dietary element categories. Validity was assessed against the FR using the Bland–Altman method and nutrient trends across MediCul score tertiles. The mean MediCul score was 54·6/100·0, with few participants reaching thresholds for key Mediterranean foods. MediCul had very good test–retest reliability (ICC=0·93, 95 % CI 0·884, 0·954, P <0·0001) with fair-to-almost-perfect agreement for classifying elements within the same category. Validity was moderate with no systematic bias between methods of measurement, according to the regression coefficient ( y =−2·30+0·17 x ) (95 % CI −0·027, 0·358; P =0·091). MediCul over-estimated the mean FR score by 6 %, with limits of agreement being under- and over-estimated by 11 and 23 %, respectively. Nutrient trends were significantly associated with increased MediCul scoring, consistent with a Mediterranean pattern. MediCul provides reliable and moderately valid information about Mediterranean diet adherence among older individuals with MCI, with potential application in future studies assessing relationships between diet and cognitive function.